PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGENTASKAN KEMISKINAN DI KELURAHAN TELUK BINJAI KECAMATAN DUMAI TIMUR KOTA DUMAI - Salam, M. Fathan; Widodo, Teguh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study evaluates the effectiveness of the Family Hope Program (PKH) in alleviating poverty in the Teluk Binjai sub-district of Dumai. Involving 79 PKH participants and utilizing a quantitative approach with simple random sampling, the data analysis indicates that the training within PKH significantly influences poverty alleviation, with a significance value of 0.000 (α < 0.05) in the t-statistic test. The simultaneous F-test confirms that PKH significantly contributes to poverty alleviation, with a significance value of 0.000. These results suggest that PKH is effective in reducing poverty levels in the area. Therefore, the program has a significant positive impact, reflecting the success of the Indonesian government's efforts to address various dimensions of poverty through initiatives such as PKH at the local level. Keywords: PKH, Poverty, Effectiveness, Society